Digital Media and Counter Narrative of Radicalism - Athik Hidayatul Ummah (Jurnal Theologia, 2020)
This article aims to describe the meaning of narratives are used by digital media or online media to counter the narrative of radicalism. The research method used is discourse analysis to find the meaning in the text. The theoretical framework used is narrative theory to explain process audience can trust about a narrative because of the consistency and truth of narrative or story. Narratives are analyzed using a framework of identity prism theory. The identity prism describes that online media as a brand has a strategy to build and promote it is unique among other brands. The results of the study are Islami.co and Ruangobrol.id have different characteristics or uniqueness and segmentation to convey the counter-narratives to the public. The narratives are built is to fight or deconstruct the narratives of radicalism-terrorism as an effort to prevent radicalism and the recruitment of new members through the internet. The counter-narrative also has coherence and truth as important standards for the public to select and judge that the narrative is consistent and credible. In the digital age, digital media have an important role in the counter-narratives of radicalism. It’s because radical-terrorist groups using the internet and social media platforms to spread their thoughts and their actions.